Los clásicos desde el Siglo de Oro: de estatuas y cortesanas en los sonetos de Quevedo sobre Friné (Polimnia 78 y 79) - Valentina Nider (Criticón, 2017)
The sonnets on Friné, the only ones dedicated to a feminine historical character in Polimnia, represent an occasion to reflect both on the peculiar “feminism” of Quevedo and on its rewriting of the classics. In addition to highlighting possible new textual allusions (especially to Athenaeum), and the probable mediation and influence of contemporary Spanish, Italian and Neo-Latin literatures, is taken into account to focus on how in the poems the Greek hetaira becomes an honest courtesan or meretrix honesta. Quevedo insists in particular on the wealth and seductive power of this typical figure of the Renaissance and Baroque era. The attraction of the sculpture of the goddess evoked in the sonnet «Si Venus hizo de oro Frine bella» is studied in the perspective of the literary tradition of «lovers of statues». Finally, we point out a possible influence of this text on Neapolitan authors of later generations of 17th Century, such as Giuseppe Battista.